Abnormal liver function tests in acute heart failure: relationship with clinical characteristics and outcome in the PROTECT study. (12th May 2016) - Biegus, Jan; Hillege, Hans L.; Postmus, Douwe; Valente, Mattia. A.E.; Bloomfield, Daniel M.; Cleland, John G.F.; Cotter, Gad; Davison, Beth A.; Dittrich, Howard C.; Fiuzat, Mona; Givertz, Michael M.; Massie, Barry M.; et al.
Abstract : Aims: Episodes of acute heart failure (AHF) unfavourably affect multiple organs, which may have an adverse impact on the outcomes. We investigated the prevalence and clinical consequences of abnormal liver function tests (LFTs) in AHF patients enrolled in the PROTECT study. Methods and results: The LFTs comprised serial assessment of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and albumin at baseline and during follow‐up (daily until discharge, on days 7 and 14). The prevalence of abnormal LFTs (above upper limit of normal for AST and ALT or below lower limit of normal for albumin) was: at baseline AST 20%, ALT 12%, albumin 40%; and at day 14: AST 15%, ALT 9%, albumin 26%. Abnormal LFTs at baseline were associated with a higher risk of in‐hospital death with odds ratios [95% confidence interval (CI)] of 3.5 (1.7–7.3) for AST, 3.9 (1.8–8.4) for ALT, and 2.8 (1.3–5.9) for albumin (all P < 0.01). Abnormal baseline and discharge LFTs had an unfavourable impact on 180‐day mortality with hazard ratios (95% CI) for baseline AST, ALT, and albumin of 1.3 (1.0–1.7), 1.1 (1.0–1.2), 1.4 (1.1–1.8), respectively, and 1.5 (1.1–2.0), 1.5 (1.0–2.2), and 1.6 (1.2–2.1), for discharge AST, ALT, albumin, respectively (all P < 0.05). Analysis of LFTs trajectories (calculated as changes in LFTs over time) revealed that increasing AST and ALT on day 3 as well as decreasing albumin on day 4 were independent prognosticators of 180‐day outcome (all P < 0.05). Conclusions: Abnormal LFTs are frequent in AHF at baseline and during hospital stay and predict worse outcomes. Whether this association is causal and what are the underlying mechanisms involved require further study.